VIABILITY OF DIDACTIC PRINCIPLES IN CONTEMPORARY PIANO EDUCATION - Stela DRĂGULIN (Studia Universitatis Babeş-Bolyai. Musica)
Our paper aims at developing a system of ideas meant to bring about excellence in the performing act, both from the perspective of the performing soloist, and in the light of the educator and trainer of young musicians, endowed with higher professional skills. In the context of our preoccupations and propensity for instrumental didactics, we have formulated the guiding lines and principles for a novel piano technique, from a contemporary perspective. We have outlined a model of interdisciplinary approach, complemented and enriched with disciplines such as biology, anatomy and physiology, biomechanics, acoustics, psychology, semiotics etc. returning therewith to the importance of didactic principles, shedding upon them the light of today’s significances for piano education. We have submitted the main goals of the didactic process in the field of piano art, establishing accordingly, premises, conditions, accomplishments and perspectives in terms of evaluation within the instrumental didactics process, particularly highlighting the self-assessment skills.